Human dental pulp stem cells (hDPSCs) promote the lipofibroblast transition in the early stage of a fibro-inflammatory process - Pisciotta, Alessandra; Di Tinco, Rosanna; Bertani, Giulia; Orlandi, Giulia; Bertoni, Laura; Pignatti, Elisa; Orciani, Monia; Sena, Paola; Bertacchini, Jessika; Salvarani, Carlo; Carnevale, Gianluca (Frontiers in Cell and Developmental Biology, 2023)
In autoimmune diseases, particularly in systemic sclerosis and chronic periaortitis, a strict correlation between chronic inflammation and fibrosis exists. Since the currently used drugs prove mostly effective in suppressing inflammation, a better comprehension of the molecular mechanisms exerted by cell types implicated in fibro-inflammation is needed to develop novel therapeutic strategies. Mesenchymal stromal/stem cells (MSCs) are being matter of deep investigation to unveil their role in the evolution of fibrogenetic process. Several findings pointed out the controversial implication of MSCs in these events, with reports lining at a beneficial effect exerted by external MSCs and others highlighting a direct contribution of resident MSCs in fibrosis progression. Human dental pulp stem cells (hDPSCs) have demonstrated to hold promise as potential therapeutic tools due to their immunomodulatory properties, which strongly support their contribution to tissue regeneration. Our present study evaluated hDPSCs response to a fibro-inflammatory microenvironment, mimicked in vitro by a transwell co-culture system with human dermal fibroblasts, at early and late culture passages, in presence of TGF-β1, a master promoter of fibrogenesis. We observed that hDPSCs, exposed to acute fibro-inflammatory stimuli, promote a myofibroblast-to-lipofibroblast transition, likely based on BMP2 dependent pathways. Conversely, when a chronic fibro-inflammatory microenvironment is generated, hDPSCs reduce their anti-fibrotic effect and acquire a pro-fibrotic phenotype. These data provide the basis for further investigations on the response of hDPSCs to varying fibro-inflammatory conditions.